Long-term observation of zooplankton biomass in the Indian Ocean sector of the Southern Ocean - Takahashi, Kazutaka; Tanimura, Atsushi; Fukuchi, Mitsuo (1998)
P(論文) Mean biomass, horizontal distribution and annual fluctuations of zooplankton biomass in the upper layer of the Indian Ocean sector of the Southern Ocean were investigated based on NORPAC standard net samples obtained by the Japanese Antarctic Research Expedition (JARE) for 22 years. The average biomasses in circumpolar areas were 36.4,79.4,133.9 and 172.5mg m^<-3> wet wt in the Subtropical, Sub-Antarctic, Antarctic, and Polar Frontal Zone, respectively. Mean zooplankton biomasses obtained in this study were slightly higher than those previously reported from Indian and other ocean sectors. In the Antarctic Zone, the average biomass decreased from north toward south. Horizontal distribution of surface zooplankton biomass showed high abundance over a relatively extensive area east of Prydz Bay, including the Polar Frontal Zone and Antarctic Zone (90-110°E, 45-65°S). The mean biomass of the Antarctic Zone varied annually. In the Antarctic Zone, the range of the variation was larger in the Northern Oceanic Community area than that in the Main Oceanic Community area, but no similarity in the patterns for the 22 years in the two areas was observed. In the Northern Oceanic community area, cyclic fluctuation of zooplankton biomass every 4-6 years were observed. This periodicity may relate to the physical process, i.e. ice-ocean-atmosphere system of the Southern Ocean. departmental bulletin paper